GENDER MARKERS AS A TOOL FOR FORENSIC MEDICAL IDENTIFICATION - Jumaniyozov Erkin Khudaiberganovich (Bright Mind Publishing, 2025)
Biological sex markers play a crucial role in forensic medical identification, particularly in cases involving mixed biological samples, sexual violence, and severely degraded or limited genetic material. The analysis of sex-specific genetic markers enables the determination of biological sex, assists in the interpretation of complex DNA mixtures, and enhances the evidentiary value of forensic genetic findings. In forensic practice, sex markers such as amelogenin, Y-chromosomal short tandem repeats (Y-STRs), and X-chromosomal markers are widely applied to differentiate male and female genetic components, especially in male–female mixtures. These markers are of particular importance in the investigation of sexual offences, missing persons cases, and disaster victim identification. Their use contributes to narrowing suspect pools and improving the accuracy of expert conclusions. Despite their advantages, the application of biological sex markers is associated with certain limitations. Genetic anomalies, mutations, deletions, and population-specific variations may affect the reliability of sex determination. In addition, interpretation challenges arise in low-template DNA samples, complex mixtures, and cases involving chimerism or intersex conditions. Therefore, careful methodological control and expert judgment are essential. This article reviews the forensic applications of biological sex markers, discusses their methodological strengths and limitations, and emphasizes the importance of integrating sex marker analysis with autosomal and mitochondrial DNA data to achieve reliable and scientifically sound forensic identification.
Keywords: Biological sex markers; forensic medicine; forensic genetics; human identification; Y-chromosomal markers; X-chromosomal markers; DNA mixtures.